Michel Foucault - Mills, Sara (Routledge, 2003)
It is impossible to imagine contemporary critical theory without the work of Michel Foucault. His radical reworkings of the concepts of power, knowledge, discourse and identity have influenced the widest possible range of theories and impacted upon disciplinary fields from literary studies to anthropology. Aimed at students approaching Foucault's texts for the first time, this volume offers: * an examination of Foucault's contexts * a guide to his key ideas * an overview of responses to his work * practical hints on 'using Foucault' * an annotated guide to his most influential works * suggestions for further reading. Challenging not just what we think but how we think, Foucault's work remains the subject of heated debate. Sara Mills' Michel Foucault offers an introduction to both the ideas and the debate, fully equipping student readers for an encounter with this most influential of thinke